Sahelin nälkäkriisin uutisointi : diskurssianalyyttinen tutkimus Helsingin Sanomien ja Ylen uutisoinnista Sahelin ruokakriisistä vuonna 2012 - Leskinen, Kati (2012)
In early 2012 the Sahel area in sub-Saharan Africa was facing shortage in food and millions of people were in risk of hunger. In my Bachelor´s thesis I´m investigating the coverage of the Sahel crisis of 2012 in two Finnish main media; the newspaper Helsingin Sanomat and the online news of Finnish broadcasting company Yle (http://yle.fi/uutiset/).